Empire's proxy American literature and U.S. imperialism in the Philippines - Wesling, Meg; De Gruyter ebooks (New York New York University Press, 2011)
Explores the literature focused schooling systems put in place by American colonizers in the Philippines during the Nineteenth Century.
Introduction: educated subjects: literary production, colonial expansion, and the pedagogical public sphere -- The alchemy of English: colonial state-building and the imperial origins of American literary study -- Empire's proxy: literary study as benevolent discipline -- Agents of assimilation: female authority, male domesticity, and the familial dramas of colonial tutelage -- The performance of patriotism: ironic affiliations and literary disruptions in Carlos Bulosan's America -- Conclusion: "An empire of letters": literary tradition, national sovereignty, and neocolonialism.
Keywords: American literature -- History and criticism. -- 19th century; Imperialism in literature; Philippine literature (English); Americans -- Philippines; American literature -- Filipino American authors -- History and criticism; National characteristics, American, in literature; United States -- Relations -- Philippines; Philippines -- Relations -- United States